STUDENTS’ INTRINSIC MOTIVATION IN LEARNING ENGLISH - Hartini, Winda; Supardi, Iwan; Bunau, Eusabinus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract This study aims to describe the Hotel Accommodation Major students’ intrinsic motivation in learning English. The subject of the research was the grade XI students of Hotel Accommodation Major at SMK 5 Pontianak in academic year 2017/2018. The researcher conducted a descriptive research on students’ level of intrinsic motivation and the most dominant factor contribute to the intrinsic motivation in learning English. The researcher gave the students questionnaire about the three factors of intrinsic motivation (challenge, emotions, and needs) and an interview were conducted to gain deeper data related to the questionnaire and the interview that they already done. The research findings showed that the students’ most dominant with high percentage of 83.25% is the Challenge Intrinsic Motivation Factor. Followed by the Needs factor with the percentage of 82.81% and Emotions factor got the lowest percentage among the other two factors with the percentage of 73.40%. Keywords: Students’ Intrinsic Motivation, Learning English, Hotel Accommodation Major, SMK 5, Descriptive Study.